Should next generation access networks fall within the scope of universal service? A EU 27 perspective - Alberto Nucciarelli; Bert M. Sadowski; Ernst-Olav Ruhle (International Telecommunications Society (ITS), 2012)
The review of the Universal Service Obligation (USO) has recently been debated in the European Union (EU). Under discussion there was the extension of the current universal service definition to include broadband access, for which some theoretical and empirical support exists. In fact the determinants of information access, which are modified by market liberalization and technological developments, challenge the traditional definition of universal service and question whether there are new frontiers for the USO in the EU. This paper looks at the origins, the theoretical arguments for, and the empirical basis of the USO in the light of the ongoing debate in the EU, and links these arguments to technological development and changing demand conditions in European broadband markets. The authors predict the inclusion of a wider set of services based on Next Generation Access networks in the EU's new regulatory approach, although in November 2011 the European Union has denied this inclusion.
Keywords: 330; European Union; universal service obligation; next generation access networks